Bridge Watchkeeping Competency and Situational Awareness Among Deck Cadets: An Assessment of Simulation-Based Training Effectiveness at STIP Jakarta - Winarno Winarno; Larsen Barasa; Meilinasari Nurhasanah Hutagaol (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Situational awareness constitutes the cognitive foundation of effective bridge watchkeeping, yet the extent to which simulator-based training programs at Indonesian maritime academies successfully develop this foundational competency among Nautika cadets has not been empirically established. This study assesses bridge watchkeeping situational awareness competency development among deck cadets at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta through a mixed-methods design combining pre- and post-simulation assessment with cadet self-assessment surveys and lecturer focus group discussions. Data were collected between April 2025 and April 2026 from 86 Nautika cadets across two academic year cohorts and nine simulator training lecturers. Thematic analysis, cross-group comparison, and narrative synthesis were applied to the qualitative data alongside quantitative competency gain analysis. Findings reveal statistically significant situational awareness competency gains following simulation training across all three Endsley model levels—perception, comprehension, and projection—with comprehension and projection dimensions showing larger absolute gains than perception, and with cadet self-assessment substantially underestimating actual competency gain relative to objective assessment results. Lecturer focus group data identified scenario complexity calibration and debrief quality as the dominant instructional factors mediating simulation training effectiveness. The study contributes an empirical baseline of simulator-based SA competency development specific to STIP Jakarta and provides evidence-based recommendations for simulation curriculum enhancement.